Modeling the Protonation States of the Catalytic Aspartates in β-Secretase - Rajamani, Ramkumar; Reynolds, Charles H (Journal of medicinal chemistry, 2004)
β-Secretase (BACE) is a critical enzyme in the production of β-amyloid, a protein that has been implicated as a potential cause of Alzheimer's disease (AD). There are two aspartic acid residues (Asp 32 and Asp 228) present in the catalytic region of BACE that can adopt multiple protonation states. The protonation state and precise location of the protons for these two residues, particularly in the presence of an inhibitor, are subjects of great interest since they have a direct bearing on the mechanism of aspartyl proteases and efforts to model β-secretase. We have carried out full liner-scaling quantum mechanical (QM) calculations that include Poisson−Boltzmann solvation in order to identify the preferred protonation state and proton location in the presence and absence of an inhibitor. These calculations favor the monoprotonated state in the presence of ligand, and di-deprotonated state in the absence of ligand. Further the proton in the monoprotonated state is located on the inner oxygen of Asp 228. These results have implications for the catalytic mechanism of BACE and related aspartyl proteases. They also provide a reference state for the protein in structure-based modeling studies of this therapeutically important target.